Table for two: fictions (Viking, Books on Tape, Penguin Publishing Group, 2024)
"The millions of readers of Amor Towles are in for a treat as he shares some of his shorter fiction: six stories set in New York City and a novella in Los Angeles. The New York stories, most of which are set around the turn of the millennium, take up everything from the death-defying acrobatics of the male ego, to the fateful consequences of brief encounters, and the delicate mechanics of comprise which operate at the heart of modern marriages. In Towles's novel, Rules of Civility, the indomitable Evelyn Ross leaves New York City in September, 1938, with the intention of returning home to Indiana. But as her train pulls into Chicago, where her parents are waiting, she instead extends her ticket to Los Angeles. Told from seven points of view, "Eve in Hollywood" describes how Eve crafts a new future for herself-and others-in the midst of Hollywood's golden age. Throughout the stories, two characters often find themselves sitting across a table for two where the direction of their futures may hinge upon what they say to each other next. Written with his signature wit, humor, and sophistication, Table for Two is another glittering addition to Towles's canon of stylish and transporting historical fiction"--

Someone saw something (Mira, 2024)
When six-year-old Gabriel vanishes from Central Park, his mother, news anchor Corina Corado, is desperate for answers. Who would take her son--and why? Detectives suspect there's a connection to the barrage of hate mail Corina's received over the years. In her line of work, it's not unusual for agitated conspiracy theorists to send messages that threaten violence...or worse. But as the investigation deepens, the secrets that Corina, her husband, Robert, and her stepdaughter, Charlotte, have kept start to unravel. As the truth behind Gabriel's disappearance emerges, Corina must race the clock to track down her missing child...before paying the ultimate price.

City of dreams: the 400-year epic history of immigrant New York (Houghton Mifflin Harcourt, HarperCollins, 2016)
With more than three million foreign-born residents today, New York has been America's defining port of entry for nearly four centuries, a magnet for transplants from all over the globe. These migrants have brought their hundreds of languages and distinct cultures to the city, and from there to the entire country. More immigrants have come to New York than all other entry points combined. City of Dreams is peopled with memorable characters both beloved and unfamiliar, whose lives unfold in rich detail: the young man from the Caribbean who passed through New York on his way to becoming a Founding Father; the ten-year-old Angelo Siciliano, from Calabria, who transformed into Charles Atlas, bodybuilder; Dominican-born Oscar de la Renta, whose couture designs have dressed first ladies from Jackie Kennedy to Michelle Obama. Tyler Anbinder's story is one of innovators and artists, revolutionaries and rioters, staggering deprivation and soaring triumphs, all playing out against the powerful backdrop of New York City, at once ever-changing and profoundly, permanently itself. City of Dreams provides a vivid sense of what New York looked like, sounded like, smelled like, and felt like over the centuries of its development and maturation into the city we know today.
Settlement , Rebellion , Anglicization , Americanization , Revolution , Republic , Famine , Irish metropolis , Kleindeutschland , Politics , War , Uprising , Transition , Liberty , Ellis Island , The Lower East Side , Little Italys , Reform , Restriction , Refuge , Renaissance , Today.